MENEPIS BUDAYA PATRIARKI DALAM PERSPEKTIF ISLAM - Bariroh, Azmil Mukhibbatul; Annisa, Firanti (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2023)
Patriarchy is a social system that places men as the main central authority figure in social organizations where the position of men is higher than that of women in all aspects of life. Patriarchal culture gives rise to various conflicts in society, especially conflicts in the household which lead to acts of violence against women. Patriarchal culture is still developing in society. Education about patriarchy and gender equality must be carried out so that society can become better and orderly. The Islamic viewpoint that patriarchy is a very contradictory system because Islam upholds justice and glorifies humans by including the position between men and woman.